CONSUMER PROTECTION IN THE MALAYSIAN DIGITAL MARKETPLACE: FROM RISKS AND CONCERNS TO A LAW REFORM - ZULHUDA, Sonny (Cyberpolitik Journal, 2025)
This paper examines the evolution of consumer protection law in Malaysia's rapidly expanding digital marketplace. With 96.4% of Malaysian households having internet access and over 78,000 entities engaged in e-commerce transactions, the digital economy now accounts for more than one-fifth of Malaysia's GDP. However, this growth has created new consumer protection challenges, with the Ministry of Domestic Trade and Cost of Living receiving nearly 8,000 e-commerce-related complaints by September 2024. The study analyses key consumer risks in digital transactions, including information asymmetry, fraudulent practices, automated decision-making systems, and limited redress mechanisms. It traces the critical 2007 amendment to the Consumer Protection Act 1999, which extended coverage to electronic transactions, and examines the comprehensive Consumer Protection (Electronic Trade Transaction) Regulations 2024. The study reveals that Malaysia has developed a sophisticated, multifaceted regulatory framework that addresses e-commerce challenges through established legal principles and emerging regulations. The paper highlights the duties imposed on online marketplace suppliers and operators, including information disclosure requirements, error rectification mechanisms, and enhanced record-keeping obligations. The study concludes that strengthening digital literacy among consumers remains crucial for effective regulatory enforcement and creating a secure digital marketplace environment.